Comparison of freeze and oven-dried oesopbageal extrusa samples for the estimation of dry matter intake and digestibility in range managed sheep - BHATTA, RAGHAVENORA; SANKHYAN, S K; SHINDE, A K; KARIM, S A (The Indian Journal of Animal Sciences, 2014)
The study was conducted to compare freeze-dried (FDE) and oven-dried (ODE) oesophageal extrusa samples for estimating in vivo dry matter intake (DMI) and digestibility using lignin ratio (LR) and in vitro DM digestibility (IVDMD) techniques in range managed sheep. Four intact and 2 oesophageal cannulated rams were allowed to graze on cenchrus pasture throughout the year. During the digestion trial conducted in winter, total faeces from 4 intact rams were collected for 5 days, by filting harness and faecal bags. During the same period diet samples were collected from 2 oesophageal-cannulated rams. Neutral detergent fibre, acid detergent fibre and acid detergent lignin contents were higher in ODE compared to FDE samples. The gross energy (GE) was higher in FDE (2 1,13 MJ/kg) than that in ODE (17.90 MJ/kg). The DMI estimated in FDE and ODE samples by LR method was 1596 and 1240 gld and by IVOMD method it was 1449 and 1236 gld, whereas, the DMD was 58.9 and 47.1 % by LR and 54.7 and 46.9 % by IVDMO techniques, respectively. Relationship between DMI and faecal output determined in FDE and ODE by LR and IVDMD methods was estimated by fitting linear regression. It is Â·concluded that IVDMD of FDE with total faecal collection is thc best method for the estimation of DMI in grazing sheep and the equation Y (DMI) = - 0.0 107 + 2.2090 X (faccal output) can be used for the estimation of DMI in range managed sheep.